1998
DOI: 10.1002/(sici)1099-0992(1998110)28:6<931::aid-ejsp904>3.0.co;2-5
|View full text |Cite
|
Sign up to set email alerts
|

Does it only depend on the point of view? Perspective-related differences in justice evaluations of negative incidents in personal relationships

Abstract: A series of four studies investigated systematic dierences between actor and recipient interpretations and justice evaluations of negative incidents in interpersonal relationships. Due to a re®ned methodology, each negative incident was assessed both by the respective recipient and actor, and each participant reported incidents from both perspectives. The studies provided clear evidence of systematic recipient-actor dierences and showed that the quality of the relationship between the parties involved in the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
35
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 35 publications
7
35
0
Order By: Relevance
“…Consistent perspective-related differences have been found in the evaluation of negative events in close relationships (e.g., Feeney & Hill, 2006;Leary, Springer, Negel, Ansell, & Evans, 1998;Mikula, Athenstaedt, Heschgl, & Heimgartner, 1998). In four studies of justice evaluations of negative incidents in close relationships, Mikula et al (1998) found recipients perceived events as more unjust and attributed more responsibility and blame to the actors than did the actors themselves.…”
Section: Perspective-related Differences In Reports Of Negative Eventssupporting
confidence: 53%
See 1 more Smart Citation
“…Consistent perspective-related differences have been found in the evaluation of negative events in close relationships (e.g., Feeney & Hill, 2006;Leary, Springer, Negel, Ansell, & Evans, 1998;Mikula, Athenstaedt, Heschgl, & Heimgartner, 1998). In four studies of justice evaluations of negative incidents in close relationships, Mikula et al (1998) found recipients perceived events as more unjust and attributed more responsibility and blame to the actors than did the actors themselves.…”
Section: Perspective-related Differences In Reports Of Negative Eventssupporting
confidence: 53%
“…In four studies of justice evaluations of negative incidents in close relationships, Mikula et al (1998) found recipients perceived events as more unjust and attributed more responsibility and blame to the actors than did the actors themselves. Similarly, previous research on victim and offender narrative accounts of interpersonal conflicts have indicated that victims describe the incident as open and continuing with lingering negative consequences, whereas offenders view the incident as over and isolated without lasting negative implications (Baumeister et al, 1990;Zechmeister & Romero, 2002).…”
Section: Perspective-related Differences In Reports Of Negative Eventsmentioning
confidence: 99%
“…Such perspective-related differences in evaluation of aggressive acts have been demonstrated in several empirical studies in school (Mummendey & Otten, 1989;Otten et al, 1995) and justice contexts (Mikula, Athenstaedt, Heschgl, & Heimgartner, 1998). Mummendey and Otten (1989) used a perspective-taking experiment and revealed that pupils in a position of aggressor considered their own behavior as less intentional and inappropriate than pupils in a position of victims.…”
mentioning
confidence: 81%
“…Mummendey and Otten (1989) used a perspective-taking experiment and revealed that pupils in a position of aggressor considered their own behavior as less intentional and inappropriate than pupils in a position of victims. In a similar vein, Mikula et al (1998) found that victims reported negative and aggressive incidents as more unjust and less justified than aggressors did. In a team-sport context, the results…”
mentioning
confidence: 85%
“…We may also consider scenarios in which the respondent is the actor instead of the actor's partner (cf. Mikula, Athenstaedt, Heschgl, & Heimgartner, 1998). The scenarios described only temporary changes regarding income, expenditures and use of time.…”
Section: Future Researchmentioning
confidence: 99%